Perceptions of Snus Among US Adult Smokers Given Free Product. Issue 1 (29th December 2016) - Meier, Ellen; Burris, Jessica L; Wahlquist, Amy; Garrett-Mayer, Elizabeth; Gray, Kevin M; Alberg, Anthony J; Cummings, K Michael; Carpenter, Matthew J
Abstract: Introduction: Snus uptake is nominal among US smokers. This longitudinal study examines (1) perceptions of snus among US smokers given free snus for 6 weeks and (2) a method for assessment of an alternative tobacco product at the population level. Methods: Adult smokers ( n = 543; 69.2% female; M age = 49.3 years), uninterested in quitting, received free snus for ad libitum use. Based on their snus use during a 6-week sampling period, participants included: (1) never users (18.4%, n = 100); (2) experimenters; that is, used ≥ once, but not during the last week of sampling (33.1%; n = 180); and (3) persistent users; that is, used ≥ once during the final week, and ≥ once during any other week of the sampling period. (48.4%; n = 263). Results: Following the sampling period, those who became persistent users were more likely than experimenters to report that switching to alternative tobacco products would lower their risk for health problems (66.5% vs. 50.0%; p = .006). Persistent users also reported greater negative affect relief and craving reduction ( p s < .001) than experimenters. Finally, persistent users were more likely than experimenters to describe snus in favorable terms with respect to ease of use, satisfaction, and liking ( p s < .05). Conclusions: Subjective experiences with snus, rather than nicotine dependence, explained experimentation versus persistent use. Even among smokers who became persistent snus users, snus was perceived as a poor substitute for cigarettes. This study design (randomized, yet naturalistic) could be extended to other novel tobacco products, including e-cigarettes, to help understand the role new products may have in the tobacco landscape. Implications: This is the first large scale, US-based naturalistic assessment of smokers' reactions to snus during an extended sampling period. This study is directly in line with FDA goals to better understand predictors of initiation, uptake, and use of other tobacco products such as snus, and serves as model for assessment methods of alternative tobacco products at the population level. Most smokers tried the provided sample of snus (approximately 82%). Subjective experiences with snus, rather than nicotine dependence, explained experimentation versus persistent use. Even among smokers who became persistent snus users, snus was perceived as a poor substitute for cigarettes.